Public Transportation Optimization on Godawari to Budanilkantha Route Via Introduction Of Bus Rapid Transit - Acharya, Sandip; Upreti, Sagar; Jha, Sandeep; Marasani, Ananda; Kattel, Suyog; Tiwari, Hemant (Journal of Advanced College of Engineering and Management, 2021)
Kathmandu is Rapidly growing city where the Crisis due to centralization is foreseen in Transportation sector due to lack of proper Planning and Vision prior of establishing settlement. The Current status of Transportation system in Kathmandu is quite alarming in absence of well-organized Public Transportation system. The growth of Vehicles and simultaneously lack of improvements of existing facilities and traffic management have resulted in unorganized improvement of Traffic thereby increasing congestion, accidents and decrease in vehicle speed affecting road capacity. So using managed Scientific system to decrease jam causing parameters with most planned system and replacing the existing Systems by modern facilities, the problem can be reduced. Introduction of Bus rapid transit by gradual replacement of old transportation systems by providing a bus lane can be promising remedial measure to optimize public transportation system in Kathmandu valley